2017
DOI: 10.4238/gmr16039620
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Molecular analysis of the GSTT1 gene polymorphism in patients with clinical manifestation of atherosclerosis.

Abstract: ABSTRACT. Atherosclerosis is a chronic inflammatory disease formed by the accumulation of lipids in the innermost layer and large-caliber artery (tunica intima). This accumulation, along with platelet factors, stimulates the proliferation of muscle cells in this region. Over than 400 genes may be related to the pathology since they regulate endothelial function, coagulation, inflammation, metabolism of amino acids, lipids, and carbohydrates. Glutathione S-transferases (GST) are enzymes that catalyze the polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…GSTs cellular detoxification activities involve in inflammatory processes, cellular differentiation and signaling pathways ( 35 37 ). Studies performed in past years have revealed that oxidative stress worsens diseases caused by inflammatory response ( 38 , 39 ). Studies demonstrated GSTs enzyme activities always depend on their genotype.…”
Section: Discussionmentioning
confidence: 99%
“…GSTs cellular detoxification activities involve in inflammatory processes, cellular differentiation and signaling pathways ( 35 37 ). Studies performed in past years have revealed that oxidative stress worsens diseases caused by inflammatory response ( 38 , 39 ). Studies demonstrated GSTs enzyme activities always depend on their genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Null mutations in GSTM1 have been associated with a large variety of diseases and an increased susceptibility to toxins [39,73]. Null mutations in GSTM1 increases the susceptibility diseases as well [40,75]. The GSTM1 present genotype was identified in a higher frequency in the Brazilian [39], Turkish [79] and British [80] population.…”
Section: Glutathione S-transferasementioning
confidence: 97%
“…They catalyze the reduced form of glutathione into xenobiotic substrates, turning such compounds more water-soluble in order to fulfill their function of detoxification [72]. GSTs polymorphisms are linked to innumerous diseases and anomalies such cancer [73], drug resistance [74], diabetes [75], atherosclerosis [39,40], and other inflammatory [76] and autoimmune diseases [77,78].…”
Section: Glutathione S-transferasementioning
confidence: 99%
See 2 more Smart Citations